El curl de bíceps en el desarrollo de la masa muscular en jóvenes. - Ortega Once, Cristhian Renato (2025)
The present study, "The Biceps Curl in Muscle Mass Development in Young People," examines the benefits of the biceps curl on muscle development for young people seeking to increase biceps fiber size. The study, conducted at the Bally Total Fitness Gym in Riobamba, Ecuador, aims to determine whether curl training is optimal for muscle development in young people. The biceps curl is an isolation exercise widely used in strength training programs due to its ability to stimulate the growth of the biceps brachii. This study analyzes the effectiveness of the biceps curl using the pyramid method for muscle hypertrophy in young people, considering parameters such as frequency, volume, intensity, and execution technique. Through a structured 12-week training plan, the goal is to evaluate progression in biceps strength and muscle size, measuring the impact of the training on physical performance. The expected results include increased muscle mass, strength, and endurance of the biceps, demonstrating that a progressive loading method can be an effective strategy for muscle development in young people seeking to improve their physical condition. Methodologically, a quantitative, quasi-experimental, field-based, and crossdisciplinary approach was used. Six chapters cover the problem statement, theoretical framework, methodology, data analysis and interpretation, conclusions and recommendations, the proposal and plans, and the annexes.